Predictors of costs associated with radical cystectomy for bladder cancer: A population‐based retrospective cohort study in the province of Quebec, Canada. Issue 2 (22nd December 2015) - Santos, Fabiano; Dragomir, Alice; Zakaria, Ahmed S.; Kassouf, Wassim; Aprikian, Armen
Abstract : Background and Objectives: There is paucity of studies on the predictors of bladder cancer (BC) management costs. We aimed to determine predictors of costs associated with radical cystectomy (RC) for BC. Methods: We conducted a retrospective analysis in a cohort of 2, 759 patients who underwent RC for BC between 2000 and 2009. We analyzed predictors of pre‐surgery, RC, post‐surgery, and total costs. The following variables were considered as potential predictors: age, gender, hospital/surgeon case load, academic hospital, and geo‐administrative region. Multivariate linear regression was used to determine predictors. Results: Predictors of pre‐surgery costs were: age (β = 808.64, P < 0.0001) and having surgery in an academic hospital (β = 511.42, P = 0.003). Increased RC costs were associated with age (β = 196.73, P = 0.0006), hospital/surgeon annual load (β = 484.45 and β = 254.21, P < 0.0001, respectively). Having surgery in academic hospitals and geographic region were significant predictors of low RC costs (β = −1085.82 and β = −449.31, P < 0.0001, respectively). Increasing age and the presence of post‐operative complications were predictors of high post‐operative costs (β = 623.48, β = 5781.44, P = 0.01, respectively), while hospital load was associated with low post‐surgery costs (β = −949.79, P < 0.0001). Conclusion: Patients' age and surgery performed by high‐volume health providers were predictive factors of high RC costs. Low RC costs were associated with surgeries performed in academic hospitals. J. Surg. Oncol. 2016;113:223–228 . © 2015 Wiley Periodicals, Inc.